EVALUASI KEBIJAKAN PEMERINTAH DAERAH KABUPATEN PELALAWAN TERHADAP PEMILIHAN KEPALA DESA DI DESA PANGKALAN PANDUK KECAMATAN KERUMUTAN KABUPATEN PELALAWAN TAHUN 2018 - Wati, Rini Ariau; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Republic of Indonesia Law No. 6 of 2014 concerning Villages that the Village Head is the village Government whose task is to carry out village governance, carry out village development, foster village community development, and empower the village community. The village head is elected directly by the village residents who are citizens of the Republic of Indonesia who meet the requirements with a term of 6 (six) years. The problem formulation in this research is how to Evaluate Government Policy on the Implementation of the Election of the Head of the Simultaneous Village in Pangkalan Panduk Village, Kerumutan District, Pelalawan Regency in 2018?               This research was conducted with the aim of describing the evaluation of the Regional Government Policy towards the implementation of the selection of the Serentak Village Head in Pangkalan Panduk Village, Kerumutan District, Pelalawan Regency in 2018. This research was a descriptive study with a qualitative approach. The location of this research was carried out in the village of Pangkalan Panduk. Data collection techniques used were observation, interviews and documentation. The data analysis technique used is descriptive and qualitative methods.The results of this study illustrate that the Regional Government Policy of Pelalawan District Against the election of the Village Head. Mr. Jahar did not receive the candidate for Village Head number 1 on the recapitulation results of the Village Head Election which was very thin because his vote was chosen because the Pangkalan Panduk Village Head election committee was cheating. The fraud was due to the refusal of voters, voters who had been registered on the Permanent Voter List and had brought invitations during the election, the Actions of the Regent who did not summon and did not facilitate a lawsuit from the candidate for the Village Head to raise objections and prove the grounds for the lawsuit in the attempt to settle the sangketa. It is known that the factors influencing the evaluation of the Pelalawan District Government's policy in the Pangkalan Panduk village because the Regent's Acts and Decisions are contrary to the prevailing laws and regulations. Second, the Regent's Decree is contrary to the general principles of good governance.Keywords: Evaluation of government policy, village head election